Effect of aqueous extract of Thymus serpyllum on lipid profile and some liver enzymes in alloxan-induced diabetic rabbit - Alamgeer, .; Mushtaq, Muhammad Naveed (Bangladesh Journal of Pharmacology, 2017)
The present study was designed to evaluate the effects of aqueous extract of Thymus serpyllum on lipid profile and some liver enzymes level in the diabetic rabbit. Rabbits were made diabetic with a single intravenous injection of alloxan and were divided into groups. Group 1 and 2 served as normal and diabetic control, respectively. Group 3 and 4 were given standard drugs glibenclamide and acarbose respectively while Group 5 was treated with 500 mg/kg of extract for 30 days. Blood samples were taken on day 0 and 30. The extract significantly reduced the level of serum cholesterol, triglyceride, LDLs, VLDLs, alkaline phosphatase and transaminases without affecting the HDLs level. Total cholesterol/HDL-cholesterol ratio was significantly reduced as compared to diabetic control. It is conceivable that T. serpyllum possesses antihyperlipidemic and hepatoprotective effects in diabetic rabbit.